2022
DOI: 10.1530/edm-21-0192
|View full text |Cite
|
Sign up to set email alerts
|

Locally invasive classical papillary thyroid carcinoma with TSH receptor I568T mutation: case report

Abstract: Summary Autonomous thyroid adenomas are caused by activating mutations in the genes encoding the thyroid-stimulating hormone receptor (TSHR) or mutations in the Gas subunit of the TSHR. Nodules with suspicious sonographic features should be submitted to fine-needle aspiration. Additional molecular testing may be performed to characterize the thyroid nodule’s malignant potential further. We present a patient who underwent whole-transcriptome RNA-sequencing that indicated a TSHR I568T mutation after an ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Therefore, to eliminate the problem of low TSHR levels, we generated clones of K1 and TPC-1 cells with controllable wt-TSHR expression, using the Lenti-X Tet-on Advanced system. The wild-type receptor was selected due to its prevalence in PTC patients and its increased constitutive activity compared to many mutations [34,35]. Plasmids were constructed containing the wild-type TSHR gene, and the successful construction was verified with DNA agarose gel electrophoresis ( Figure A2a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to eliminate the problem of low TSHR levels, we generated clones of K1 and TPC-1 cells with controllable wt-TSHR expression, using the Lenti-X Tet-on Advanced system. The wild-type receptor was selected due to its prevalence in PTC patients and its increased constitutive activity compared to many mutations [34,35]. Plasmids were constructed containing the wild-type TSHR gene, and the successful construction was verified with DNA agarose gel electrophoresis ( Figure A2a ).…”
Section: Resultsmentioning
confidence: 99%
“…To multiply the TSH signal reception, cell clones were created to overexpress the TSHR receptor in a controllable manner. Instead of using mutant types of the TSHR gene (many of which have been reported), the wild type allele was selected since most TSHR mutations are associated with follicular thyroid carcinoma (FTC) much more often compared to PTC, where mutations are relatively rare [34]. Additionally, wild-type TSHR ( wt-TSHR ) has been reported to possess a high level of constitutive activity in the wild-type form [35]; thus, overexpressing would significantly multiply signal reception and transduction.…”
Section: Methodsmentioning
confidence: 99%
“…This study was inspired by a query after the management of an aggressive case of PTC where the index lesion was positive for a TSHRpI568T mutation ( 12 ). We showed that this variant is extremely rare, representing only ~0.7% of all molecular findings in the Afirma database.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was influenced by an interesting case report of an aggressive thyroid malignancy with a TSHRpI568T mutation ( 12 ). Briefly, a 53-year-old female underwent a fine needle aspiration biopsy (FNAB) of a thyroid nodule with resultant Bethesda V cytology and Afirma ® Xpression Atlas (XA) testing that revealed a TSHRpI568T mutation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%